Seismic demands of bare and base-isolated steel frames for real against simulated records of a past earthquake. Issue 9 (2nd September 2022) - Ozsarac, Volkan; Karimzadeh, Shaghayegh; Askan, Aysegul; Erberik, Murat Altug
Abstract: A challenging task in earthquake engineering is investigation of engineering demand parameters under regional records of large earthquakes due to inherently low frequency of these events. Use of simulated records in such cases is a recent alternative. Ground motion simulations were traditionally performed to model physical processes in earthquake occurrences. Nowadays, simulations are also used for engineering purposes. However, detailed assessment of simulated records against real data including their effect on structural response is necessary. The aim herein is to explore how alternative simulation methods differ in terms of engineering demand parameters for multi-degree-of-freedom models and to find out their efficiency in design and assessment of base isolated structures. For this purpose, bare and base-isolated models of a 6-story steel moment-resisting frame are considered. Force-based, displacement-based and energy-based demands are evaluated due to real and simulated records of 2009 L′Aquila (Italy) event (Mw = 6.3). Ground motion simulation approaches include stochastic finite-fault method and hybrid integral-composite techniques. Analyses show that when seismological misfits between the real and simulated records are smaller, closer matches between their engineering demand parameters are observed. Finally, numerical results reveal that simulated motions validated against real data provide alternative sets particularly for regions with sparse observed records.